Design and Implementation of a High Gain Hexagon Loop Antenna for 5G and WLAN Application - Al-Zahrani, Ali Y.; Najim, Mohd (Engineering, Technology & Applied Science Research, 2024)
In this work, the design and implementation of a high-gain Hexagon Loop Antenna (HLA) for 5G and WLAN application is presented. Initially, a hexagon patch was designed to resonate at 3.5 GHz. A loop-based radiator was tailored to obtain miniaturization without affecting the overall performance of the proposed antenna. A CPW feed was utilized to maintain the wide bandwidth with improved return loss. FR-4 material was used as a dielectric to retain the low cost of the antenna. The return loss was kept well below -10 dB, from 3.2 GHz to 6.4 GHz. The gain of the proposed Microstrip Hexagon Loop Antenna (MHLA) is 5.3 dBi at 3.5 GHz and 8.2 dBi at 5.8 GHz, respectively. To improve the gain and directivity of the proposed antenna, a square-shaped AMC unit cell was considered, and finally, a [4×4] ground plane AMC was integrated with the antenna. The radiation pattern of the antenna is stable and low cross-polarization is maintained for the desired band. A simulation of the proposed antenna was carried out in the ANSYS HFSS tool and the experimental results were measured inside an anechoic chamber. The experimental and simulated results of the proposed antenna are in good agreement. Its simple and low-profile structure, lower cost, and high gain ensure that the proposed high gain antenna is well suited for sub-6 GHz band and wireless application.